Main Factors for Human Capital Reproduction - СинявскаяОксана Вячеславовна (Journal of Economic Sociology, 2010)
The paper is devoted to the reproduction of human capital in the system formal school education. The basic framework of the study is the idea of «social embeddedness» of economic action, which allowed authors to widen the list of factors that influence the diversity of the human capital capacity and to add new determinants to the individual abilities, family income, and socio-economic status of the parents. The theoretical framework and the secondary analysis of the empirical studies disclosed the following factors of human capital reproduction: 1) restricting determinants such as, type o settlement, level of its urbanization, education model (competitive or encouraging) and family financial resources; 2) the factors of success and educational period, such as social capital (family, neighbors, friends); 3) parents’ human capital, financial family capital, gender and ethnical differences, type of school. Further analysis of empirical data for Russia showed that the same factors could be revealed but their effect might be different.